Temporal statement modifiers. - Böhlen, Michael H.; Jensen, Christian S.; Snodgrass, Richard Thomas
A wide range of database applications manage time-varying data. Many temporal query languages have been proposed, each one the result of many carefully made yet subtly interacting design decisions. In this article we advocate a different approach to articulating a set of requirements, or desiderata, that directly imply the syntactic structure and core semantics of a temporal extension of an (arbitrary) nontemporal query language. These desiderata facilitate transitioning applications from a nontemporal query language and data model, which has received only scant attention thus far. The paper then introduces the notion of statement modifiers that provide a means of systematically adding temporal support to an existing query language. Statement modifiers apply to all query language statements, for example, queries, cursor definitions, integrity constraints, assertions, views, and data manipulation statements. We also provide a way to systematically add temporal support to an existing implementation. The result is a temporal query language syntax, semantics, and implementation that derives from first principles. We exemplify this approach by extending SQL-92 with statement modifiers. This extended language, termed ATSQL, is formally defined via a denotational-semantics-style mapping of temporal statements to expressions using a combination of temporal and conventional relational algebraic operators.
Keywords: ATQSL; Statement modifiers; Temporal databases